Covering Conventional and Unconventional Religion: A Reporter's View - Dart, John (Review of religious research, 1997)
Critics of news coverage should probably know that these days one would hardly hear an editor shout "Stop the presses!" to some dungeon deep in the bowels of the "Daily Bugle" just to grab a sensational headline. The anachronistic image dates from at least mid-century when many large cities had several newspapers with multiple editions, each competing for streetcorner attention and vying to scoop the opposition. For various social and economic reasons -- suburban sprawl, increased commuter travel, production and distribution costs, vast improvements in electronic communications, corporate mergers and buyouts -- the major cities now have one or two newspapers and different kinds of competitors in television news and suburban papers. Yet this is precisely one of the explanations offered for media bias (sensationalism driven by profit motive) in the paper by Richardson and Van Driel (this issue). The authors' claim invites a closer inspection of how news is produced and disseminated.